FRI0233 The retention rates of abatacept in elderly ra patients (65 years and above) who cannot be treated with methotrexate: comparison with etanercept and tocilizumab; a single-center, retrospective, case-control study. (15th June 2017) - Kikuchi, E; Aoki, N; Yoshioka, T; Okai, T
Abstract : Background: There are many elderly rheumatoid arthritis (RA) patients who cannot be treated with methotrexate (MTX) for many reasons, but data about the therapeutic strategies by biologic agents for the patients are insufficient. Objectives: To analyze the retention rate of abatacept in elderly patients with RA who cannot be treated with MTX. Methods: Data were retrospectively collected from the medical records of patients with rheumatoid arthritis at our center. Abatacept (ABT), etanercept (ETN), or tocilizumab (TCZ) was administered to 68 elderly RA patients who could not be treated with MTX. We analyzed the retention rate of each group by Kaplan–Meier curves and the log-rank test. The primary end point was the 24-month retention rate of the biologics without discontinuation due to adverse events, loss or primary lack of effectiveness. Results: In the ABT group (26 cases: a mean age of 77.8±6.3 years, ACPA positive 92.3%, oral steroid use 34.6%), the cumulative retention rates for both 12 and 24 months were 0.699. In the ETN group (26 cases: a mean age of 75.8±5.1 years, ACPA positive 92.0%, oral steroid use 73.1%), the cumulative retention rates for 12 and 24 months were 0.450 and 0.315, respectively. In the TCZ group (16 cases: a mean age of 73.7±5.6 years, ACPA positive 87.5%, oral steroid use 56.3%), the cumulative retention rates for 12 and 24 months were 0.433 and 0.325, respectively. There was a significant difference in the retention rates between ABT groups and the other two groups [log-rank test, p =0.018 (ABT vs. ETN), 0.047 (ABT vs. TCZ)]. There are no significant retention rates between ETN groups and TCZ groups. Three cases (11.5%) in the ABT group were discontinued the biologic agents by hospitalization for severe infection within 24 months. Five cases (19.2%) in the ETN group, six cases (37.5%) in TCZ group were hospitalized for severe infection, respectively. Conclusions: Our data suggested that abatacept can be used for a period longer than etanercept or tocilizumab for elderly RA patients who cannot be treated with methotrexate. References: Harigai, et al. Mod Rheumatol. 2016 Jul 3; 26(4): 491–498. Disclosure of Interest: None declared